AABIP Evidence-informed Guidelines and Expert Panel Report for the Management of Indwelling Pleural Catheters. Issue 4 (October 2020) - Miller, Russell J.; Chrissian, Ara A.; Lee, Y.C. Gary; Rahman, Najib M.; Wahidi, Momen M.; Tremblay, Alain; Hsia, David W.; Almeida, Francisco A.; Shojaee, Samira; Mudambi, Lakshmi; Belanger, Adam R.; Bedi, Harmeet; et al.
Abstract : Background: While the efficacy of Indwelling pleural catheters for palliation of malignant pleural effusions is supported by relatively robust evidence, there is less clarity surrounding the postinsertion management. Methods: The Trustworthy Consensus-Based Statement approach was utilized to develop unbiased, scientifically valid guidance for the management of patients with malignant effusions treated with indwelling pleural catheters. A comprehensive electronic database search of PubMed was performed based on a priori crafted PICO questions (Population/Intervention/Comparator/Outcomes paradigm). Manual searches of the literature were performed to identify additional relevant literature. Dual screenings at the title, abstract, and full-text levels were performed. Identified studies were then assessed for quality based on a combination of validated tools. Appropriateness for data pooling and formation of evidence-based recommendations was assessed using predetermined criteria. All panel members participated in development of the final recommendations utilizing the modified Delphi technique. Results: A total of 7 studies were identified for formal quality assessment, all of which were deemed to have a high risk of bias. There was insufficient evidence to allow for data pooling and formation of any evidence-based recommendations. Panel consensus resulted in 11 ungraded consensus-based recommendations. Conclusion: This manuscript was developed to provide clinicians with guidance on the management of patients with indwelling pleural catheters placed for palliation of malignant pleural effusions. Through a systematic and rigorous process, management suggestions were developed based on the best available evidence with augmentation by expert opinion when necessary. In addition, these guidelines highlight important gaps in knowledge which require further study. Abstract : Supplemental Digital Content is available in the text.